Do-It-Yourself Medicine? The Impact of Light Cannabis Liberalization on Prescription Drugs - Vincenzo Carrieri; Leonardo Madio; Francesco Principe (Institute of Labor Economics (IZA), 2020)
Governments worldwide are increasingly concerned about the booming CBD (cannabidiol) products. However, little is known about the impact of their liberalization. We study a unique case of unintended liberalization of a CBD-based product (light cannabis) that occurred in Italy in 2017. Using unique and high-frequency data on prescription drug sales and by exploiting the staggered local availability of the new product in each Italian province, we document a significant substitution effect between light cannabis and anxiolytics, sedatives, opioids, anti-depressants, and antipsychotics. Such medical non-adherence is consistent with a self-medication interpretation. Results are informative for regulators and suggest that policies contrasting this "green oil" boom risk to disregard the effective need of patients to seek effective reliefs of their symptoms.
Keywords: H51; H75; I18; K32; K42; 330; light cannabis; self-medication; marijuana; difference-in-difference; prescription drugs; CBD